Global Surgery: Burn Outreach by Shriners Children's Texas - Zapata-Sirvent, Ramon L.; Branski, Ludwik K.; Lee, Jong O. (Seminars in Plastic Surgery, 2024)
Global surgery describes a rapidly developing field that seeks to improve surgical treatment internationally, specifically in those specialized treatments that are not readily accessible, considered complex and expensive. Burns cause 300,000 deaths annually, 90% of which occur in low- and middle-income countries (LMICs).Burns are a public health problem since they can cause disability and death. Shriners Children's Texas is a unique model of global surgery for an important number of countries in Central and South Americas and Mexico, providing specialized acute burn care with low mortality for burned children.Survivors of severe burns may face devastating sequelae due to burn scar contractures and hypertrophic burn scars that may limit the social reintegration. Burn reconstruction is not easily accessible to patients in LMICs. After discharge from acute burn treatment at our hospital, patients may return every 6 months for in-person follow-up to assess any surgical, psychological, or rehabilitative needs. Telemedicine allows for monitoring of postoperative results and evaluation for new surgical procedures. Follow-up clinic visits called outreach clinics held in international hospitals or international Shriners Temples allow for evaluation of follow-up patients and new patients with reconstructive needs that may benefit from a treatment in Shriners Children's Texas in Galveston, Texas.
Keywords: global surgery; Burn outreach; burn disaster; pediatric